Policy Implementation of Acehnese Culture Local Content Curriculum Based on Islamic Sharia In Tsanawiyah State Madrasah Bireuen District - Ilwan, Ilwan; Asari, Hasan; Wijaya, Candra (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This study aims to uncover and analyze the implementation of Acehnese cultural local content curriculum policies in accordance with Islamic law in Madrasah Tsanawiyah Bireuen District. This research uses qualitative methods, and the approach used is a phenomenological approach. Data collection techniques using interview techniques, observation, and document studies. The analysis of the research data uses the steps proposed by Miles and Hubermun, which include data reduction, data presentation, and conclusions. In strengthening the validity of the data findings and research authenticity, the researcher refers to the use of data validity standards suggested by Lincoln & Guba (1985), which consist of credibility, transferability, dependability, and comfirmability. The results of this study indicate that the implementation of Acehnese cultural local content curriculum policies according to Islamic law in Madrasah Tsanawiyah Bireuen Regency refers to Qanun No. 14 of 2014 concerning the Implementation of Education, which explains that local content subjects consist of 1) regional languages; 2) history of Aceh; 3) customs, culture, and local wisdom; and 4) skills education. The implementation of this local content curriculum policy is also regulated through Law No. 11 of 2006 concerning the Government of Aceh (UUPA) and the Aceh Traditional Council (MAA) by creating a youth training program for traditional pioneers, training for traditional leaders, and other traditional institutions.